Design Of Inventory Information System At Polda Kepri Information Technology And Communication Division Of Polda Kepri - Riyan Fajri Ramadhan; Sherly Agustini (Rey Media Grafika, 2024)
Inventory management in government agencies such as the Riau Islands Police is an important aspect to ensure effective and efficient asset recording and monitoring. Manual management often faces obstacles such as recording errors and potential asset loss. Therefore, a technology-based information system is needed that can improve efficiency and transparency. This study aims to design a Laravel-based inventory information system in the Information and Communication Technology (ICT) Sector of the Riau Islands Police. This system allows users to manage inventory digitally, including asset recording, borrowing, returning, and monitoring status in real time. The system development uses the Rapid Application Development (RAD) method which accelerates the development process with an iterative approach. The results of the study show that the designed system is able to improve the efficiency of asset recording and monitoring, minimize data errors, and simplify the inventory audit and reporting process. With this system, it is expected to support the digitalization of administration in the Riau Islands Police environment and increase accountability in the management of technology assets.